BOSNIAN MUSLIMS AND SERBS - REASONS FOR DISPUTE FROM 1918 TO THE PRESENT DAY - Todorović, Vladica S. (Politeia, 2020)
The paper provides an analysis of political relations of Bosnian Muslims (officially Bosniaks since 1993) and Serbs, lasting for almost a century. Firstly, the author deals with their relations in the Kingdom of Serbs, Croats, and Slovenes and the Kingdom of Yugoslavia from 1918 to 1941, all the way through World War II from 1941 to 1945, then in the Communist Yugoslavia from 1945 to 1990, followed bythe period after the break-up of Socialist Federal Republic Yugoslavia, when Bosnia and Herzegovina became sovereign state, and, finally,with their current relations We believe that the main cause of the dispute is that Bosnian Muslims historically always abandoned Serbs at critical times and sought the support of other states and nations for their state-building goals. In wars, they supported their enemies, often forming alliances with other states or nations. As religious idea among the Bosnian Muslims grew from 1918, so did their numbers as well as their aspirations for Serbian territories. Similarly, as the number of Bosnian Muslims grew, so did the interest of great powers and political parties as well as their military support. Most importantly, with the rise of numbers of Bosnian Muslims, their policies and their stance towards the state changed. Hence, when they became majority in Bosnia and Herzegovina, they wanted to turn the Republic of Bosnia and Herzegovina into their national state.